Purification of supercoiled plasmid DNA from clarified bacterial lysate by arginine‐affinity chromatography: Effects of spacer arms and ligand density. Issue 12 (2nd May 2014) - Bai, Jin‐Shan; Bai, Shu; Shi, Qing‐Hong; Sun, Yan
<x xml:space="preserve">Abstract</x> Efficient loading on a chromatographic column is the dilemma of the process development faced by engineers in plasmid DNA purification. In this research, novel arginine‐affinity chromatographic beads were prepared to investigate the effect of spacer arm and ligand density to their chromatographic performance for the purification of plasmid. The result indicated that dynamic binding capacity for plasmid increased with an increasing ligand density and carbon number of spacer arm, and the highest binding capacity for plasmid of 6.32 mg/mL bead was observed in the column of arginine bead with a ligand density of 47 mmol/L and 10‐atom carbon spacer. Furthermore, this arginine bead exhibited better selectivity to supercoiled (sc) plasmid. The evidence of a linear gradient elution suggested further that the binding of plasmid on arginine beads was driven by electrostatic interaction and hydrogen bonding. Hence, sc plasmid could successfully be purified from clarified lysate by two‐stepwise elution of salt concentration. By the refinement of the elution scheme and loading volume of clarified lysate, the column of arginine bead with a ligand density of 47 mmol/L exhibited the highest recovery yield and a much higher productivity among arginine‐affinity columns. Therefore, reshaped arginine beads provided more feasible and practical application in the preparation of sc plasmid from clarified lysate.